2012
DOI: 10.1038/jhg.2012.127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ZNF350/ZBRK1 promoter variants and breast cancer susceptibility in non-BRCA1/2 French Canadian breast cancer families

Abstract: ZNF350/ZBRK1 is a transcription factor, which associates with BRCA1 to co-repress GADD45A to regulate DNA damage repair, and the expression of ZNF350 is altered in different human carcinomas. In a previous study, we identified ZNF350 genomic variants potentially involved in breast cancer susceptibility in high-risk non-BRCA1/2 breast cancer individuals, which pointed toward a potential association for variants in the 5'-UTR and promoter regions. Therefore, direct sequencing was undertaken and identified 12 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Additionally, ZNF350/ZBRK1 (Zinc-finger and BRCA1-interacting protein with a KRAB domain 1), which associates with BRCA1 to regulate the transcription of DNA damage response genes, such as GADD45A, p21, Bax, and GADD153, is potentially involved in breast cancer susceptibility. 28,29 ZNF703, as a novel oncogene, its high expression triggers poor survival in luminal B breast cancer patients and further study shows ZNF703 can be up-regulated by long non-coding RNA SPRY4-IT1. [30][31][32] Another set of publications point to the involvement of ZNFs in clinical treatment.…”
Section: Breast Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, ZNF350/ZBRK1 (Zinc-finger and BRCA1-interacting protein with a KRAB domain 1), which associates with BRCA1 to regulate the transcription of DNA damage response genes, such as GADD45A, p21, Bax, and GADD153, is potentially involved in breast cancer susceptibility. 28,29 ZNF703, as a novel oncogene, its high expression triggers poor survival in luminal B breast cancer patients and further study shows ZNF703 can be up-regulated by long non-coding RNA SPRY4-IT1. [30][31][32] Another set of publications point to the involvement of ZNFs in clinical treatment.…”
Section: Breast Cancermentioning
confidence: 96%
“…Moreover, ZNFs can also improve breast cancer cell survival by regulating cellular autophagy, such as ZNF143 regulating the p53‐Beclin1 axis, 26 ZNF32 activating the AKT/mTOR pathway, 27 respectively. Additionally, ZNF350/ZBRK1 (Zinc‐finger and BRCA1‐interacting protein with a KRAB domain 1), which associates with BRCA1 to regulate the transcription of DNA damage response genes, such as GADD45A, p21, Bax, and GADD153, is potentially involved in breast cancer susceptibility 28,29 . ZNF703, as a novel oncogene, its high expression triggers poor survival in luminal B breast cancer patients and further study shows ZNF703 can be up‐regulated by long non‐coding RNA SPRY4‐IT1 30–32 …”
Section: Role Of Znfs In Different Tumorsmentioning
confidence: 99%
“…An interesting study by Lo et al demonstrated that, in many cases, it is not the effect of mutations in one single gene, but rather a cumulative effect of SNPs in 16 BRCA1/2 interactors, namely, CASP8, BARD1, PIK3CA, ESR1, RB1CC1, TCG101, SLC22A18, ATM, PALB2, KRAS2, RAD51, TP53, PHB, BRIP1, PPM1D and CHEK2 [14]. Another study has shown that the c.1518C>T variant in BARD1, a BRCA1 interactor, increases the risk of BC [15], while a possible role of ZBRK1 variants/haplotypes and ZNF350 promoter variants in intermediate BC risk has been suggested [16,17]. Other BRCA1/2 interactors were also studied, many having no effect on BC predisposition [18,19].…”
Section: Non-linear Progressionmentioning
confidence: 99%